FLOOD FREQUENCY ANALYSIS IN THE CATCHMENT OF OUED MAZAFRAN IN THE NORTHERN OF ALGERIA - SUICI, Elkheir; YAHIAOUI, Abdelhalim; EL-MEDDAHI, Yamina (GeoScience Engineering, 2024)
Extreme flood events are commonly described by several dependent characteristics, such as duration, volume and peak flow. In Algeria and North Africa, flood frequency analysis is conducted as a univariate approach focusing separately on each single of flood characteristics. The analysis of flood in oued Mazafran catchment by the flood frequency analysis is crucial for understanding and managing flood risk, designing infrastructure and planning for floodplain management. To perform flood frequency analysis, the series of the annual maximum flow discharge of Fer a Cheval station is fitted to a probability distribution. Well, several probability distributions can be used to fit this series such as Gumbel, Log Normal, Log Pearson type III, and more. The Choosing a single distribution probability has become an important question in hydrology frequency analysis. Therefore, the use of the decision support system that is based on the heavy tails of distribution probability analysis conducts to the use of sub-exponential distributions and information Criterion to the Gumbel distribution for this analysis.